Application possibilities of RTLS system in production logistics - Tamás, Péter; Tamás, Bátori (Journal of Production Engineering, 2021)
Determining the current position of objects in logistics processes (products, unit loads, forklifts, etc.) is the basis for new process development and optimization opportunities (e.g., development of storage strategy, forklift route planning, etc.) that significantly affect the competitiveness of companies. Background information systems that provide real-time data using localization, - or called RTLS (Real Time Location System),- are becoming more widespread. In the dissertation I summarize the operation, physical realization, conditions of use and advantages of a real-time technology that can be applied to a warehouse serving its production, as well as the steps of a possible implementation.